Stable isotope composition (δ18O, δ2H) of river runoff, groundwater and precipitation at the Sosna River, Elets - Julia N Chizhova; Maria B Kireeva; Ekaterina P Rets; Alexey A Ekaykin; Anna Kozachek; Arina N Veres; Natalia Varentsova; Artem Gorbarenko; Timofey Samsonov; Nikita Povalyaev; Maxim Kharlamov; Valentina Plotnikova (PANGAEA, 2022)
Empirical study of the isotopic features of river runoff were carried out at three hydrological posts in 3 different river basins: the Zakza river in the southwest of the Moscow region, the Dubna river in the north of the Moscow region and the Sosna river in the Voronezh region. Samples of river water, groundwater and precipitation were collected at weekly intervals from September 2019 to October 2021. The analysis was performed by a Picarro L2130-i isotope analyzer. The accuracy was 0.04 extperthousand for δ18 and 0.1 extperthousand for δ2. The values are calibrated in the VSMOW-VSLAP scale.
In: Chizhova, JN et al. (2022): Stable isotope composition (δ18O, δ2H) of river runoff, groundwater and precipitation at three hydrological stations in the European part of Russia [dataset publication series]. PANGAEA, https://doi.org/10.1594/PANGAEA.942291